IMPROVING STUDENTS' SELF DISCLOSURE SKILLS THROUGH JOHARI WINDOW TECHNIQUE - Mondang Munthe (Sean Institute, 2022)
Self Disclosure is sharing personal information including thoughts, feelings, personal opinions and also information that is hidden from others. The Johari Window technique is a technique whose purpose is to make someone open themselves, which is open to others and open to others so as to create good relationships between individuals. This study aims to determine whether self-disclosure or student openness can be improved through the Johari Window technique. This research uses experimental research method with one group pretest-posttest design. The source of research data was students of class VIII-A SMP Negeri 2 Gunungsitoli Utara. The instruments in this study were tests and observations. Data analysis was carried out by analyzing the results of pre-test, post-test and observation per individual.